Analisis Pengaruh Tata Kelola Perusahaan Terhadap Aktivitas Penghindaran Pajak - Hendi Hendi; Dea Fanny (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
This study aims to determine the effect of corporate governance consisting of executive compensation variables, executive characteristics or characteristics, company size, institutional ownership, the proportion of the board of commissioners, audit committee, and audit quality applied to companies against tax avoidance measures as measured by ETR (Effective Tax Rate). Stakeholders such as investors, potential investors, and especially company management also need to know the importance of applying good corporate governance to companies, especially to minimize tax avoidance. The sample of this study amounted to 607 secondary data from a total of 150 non-financial companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period and did not include companies engaged in property, real estate, and construction. Data were analyzed using panel regression method and processed using SPSS and Eviews software. The results obtained from this study shows that executive compensation variables and audit quality significantly positive effect on ETR or have a negative influence on tax avoidance. Variable executive characteristics and firm size have a significant negative effect on ETR or have a positive influence on tax avoidance. While other variables, namely institutional ownership, number of independent commissioners, and audit committees do not seem to have a significant effect on tax avoidance.